Pengaruh Sistem E-Filling, Pemahaman Perpajakan, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM (Studi Kasus Pada Pelaku Umkm Di Kecamatan Brangsong Kendal) - Devarila Wulandini; Ceacilia Srimindarti (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Tax is one of the main targets set by the government as a source of state revenue. This study aims to determine the effect of the e-filling system, understanding of taxation, and tax sanctions on taxpayer compliance with MSME actors in Brangsong Kendal District. The type of data used is the type of primary data. The sampling technique used in this study used accidental sampling. A total of 100 MSME taxpayers were selected as respondents using the survey method. Data analysis technique using multiple linear regression analysis. The results of the study show that the E-filling system has a positive and significant effect on MSME taxpayer compliance. Understanding of Taxation has no effect on MSME Taxpayer Compliance. Tax sanctions have a positive and significant effect on MSME taxpayer compliance. Keywords: Understanding of Taxation, Tax Sanctions, E-filling System